Optimization of Halal Capsule Shell Combination of Amylopectin of Cassava (Manihot esculenta) Pell and Caragenan of Euchema cottoni - Arika Putri Pratiwi; Syarifah Nur Hazlia; Siti Hartinah Yulianto; Wakhidatus Shifa Syururin; Nurul Marfu'ah (Media Farmasi: Jurnal Ilmu Farmasi, 2025)
Gelatin, a primary material for capsule shells, is predominantly sourced from pigs, raising significant concerns regarding its halal status for Muslim consumers. Therefore, identifying halal and sustainable alternatives to gelatin is crucial for the pharmaceutical industry. This study aimed to formulate and evaluate halal capsule shell preparations combining amylopectin from cassava (Manihot esculenta) peel starch and carrageenan from Euchema cottoni. The research utilized an experimental quantitative design with five formulations (F1–F5) based on varying amylopectin: carrageenan concentrations, namely 0.5%:3% (F1), 1%:3% (F2), 1.5%:3% (F3), 0%:3% (F4), and 3%:0% (F5). The capsule shells were assessed through specification tests, water content, ash content, and disintegration time. Data were analyzed using one-way ANOVA in SPSS version 26.0 at a 95% confidence level. The results showed that all formulations met the standards for water content (20–60%), ash content (<5%), and disintegration time (<30 minutes) based on PT. Kapsulindo Indonesia and the Indonesian Pharmacopoeia. However, none of the formulations fully met the specifications for capsule body diameter, cap diameter, and total length, primarily due to manual molding limitations. Among the five formulations, F3 demonstrated the closest conformity to standard physical parameters. Statistical analysis indicated that variations in the concentration of cassava peel starch and Euchema cottoni carrageenan significantly influenced capsule shell specifications, moisture content, and disintegration time (p<0.05), while having no significant effect on ash content (p>0.05). In conclusion, the combination of cassava peel amylopectin and Euchema cottoni carrageenan shows promising potential as a halal and eco-friendly alternative to gelatin-based capsule shells. Further optimization using automated molding systems is recommended to achieve standardized dimensions for commercial application.